THE IMPACT OF SOCIAL REHABILITATION ON PRISONERS IN NARCOTICS PRISON CLASS IIA PEMATANG SIANTAR - Tando, Cahyoko Edi; Damanik, Rismanto Agustian (ANAYASA : Journal of Legal Studies, 2024)
This rehabilitation goal is in line with the correctional system which focuses more on improving the behavior and morals of individuals who violate the law. This research method is qualitative, aiming to describe social phenomena from the participant's perspective and produce descriptive data through interviews, field notes, and data analysis to understand the phenomenon being studied. The results of interviews with drivers at the Class IIA Pematang Siantar prison showed that the social rehabilitation program had a positive impact in the form of changes in thought patterns, increased happiness, emotional control, clearer thinking, reduced stress, recovery from trauma, improved appearance, good social relationships, motivation. Looking for work, and the desire for a better life after release. There are also several factors supporting the progress of social rehabilitation in the Pematang Siantar Class IIA Narcotics Prison.